Fluid Inclusion and Oxygen Isotope Constraints on the Origin and Hydrothermal Evolution of the Haisugou Porphyry Mo Deposit in the Northern Xilamulun District, NE China - Qihai Shu; Yong Lai (Geofluids)
The Haisugou porphyry Mo deposit is located in the northern Xilamulun district, northeastern China. Based on alteration and mineralization styles and crosscutting relationships, the hydrothermal evolution in Haisugou can be divided into three stages: an early potassic alteration stage with no significant metal deposition, a synmineralization sericite-chlorite alteration stage with extensive Mo precipitation, and a postmineralization stage characterized by barren quartz and minor calcite and fluorite. The coexistence of high-salinity brine inclusions with low-salinity inclusions both in potassic alteration stage (~440°C) and locally in the early time of mineralization stage (380–320°C) indicates the occurrence of fluid boiling. The positive correlations between the homogenization temperatures and the salinities of the fluids and the low oxygen isotopic compositions (δ18Ofluid < 3‰) of the syn- to postmineralization quartz together suggest the mixing of magmatic fluids with meteoric water, which dominated the whole mineralization process. The early boiling fluids were not responsible for ore precipitation, whereas the mixing with meteoric water, which resulted in temperature decrease and dilution that significantly reduced the metal solubility, should have played the major role in Mo mineralization. Combined fluid inclusion microthermometry and chlorite geothermometer results reveal that ore deposition mainly occurred between 350 and 290°C in Haisugou.